2-(2,5-Dichlorobenzenesulfonamido)-3-methylbutanoic acid - Khan, I.U.; John, P.; Iqbal, H.; Sharif, S.; Tiekink, E.R.T. (International Union of Crystallography, 2010)
The structure of the title compound, C11H13Cl2NO4S, shows one sulfonamide-O atom to lie almost in the plane of the benzene ring [C-C-S-O = -178.7 (2) degrees] and the other to one side [C-C-S-O = -49.4 (3)degrees]. Lying to the other side is the amine residue, which occupies a position almost perpendicular to the plane [C-S-N-C = 70.2 (2)degrees]; the carboxylic acid group is orientated to lie over the benzene ring. In the crystal, the appearance of an 11-membered {center dot center dot center dot OH center dot center dot center dot OCOH center dot center dot center dot OC2NH} synthon, which features the hydroxy group forming both donor (to a carbonyl-O) and acceptor (from the amine-H) interactions, leads to the formation of a supramolecular chain along the a axis. Chains are connected in the crystal structure by C-H center dot center dot center dot O contacts.